2010
DOI: 10.1080/10986065.2010.482150
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Development of Flexibility in Struggling Algebra Students

Abstract: The ability to flexibly solve problems is considered an important outcome for school mathematics and is the focus of this paper. The paper describes the impact of a three-week summer course for students who struggle with algebra. During the course, students regularly compared and contrasted worked examples of algebra problems in order to promote flexible use of solution strategies. Assessments were designed to capture both knowledge and use of multiple strategies. The students were interviewed in order to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…The Rittle-Johnson and Star measure of strategic flexibility directs students to generate multiple solution paths; however, in a tutoring setting students are not prompted to choose multiple strategies. Studies of strategic flexibility have observed that when students are not asked to generate multiple strategies they will often use only one strategy to solve problems [4,6]. This makes it difficult to observe flexible strategy use indirectly.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The Rittle-Johnson and Star measure of strategic flexibility directs students to generate multiple solution paths; however, in a tutoring setting students are not prompted to choose multiple strategies. Studies of strategic flexibility have observed that when students are not asked to generate multiple strategies they will often use only one strategy to solve problems [4,6]. This makes it difficult to observe flexible strategy use indirectly.…”
Section: Discussionmentioning
confidence: 99%
“…Without instructing students to solve problems using multiple strategies, the likelihood of a student using a divergent strategy is low. Previous research on strategic flexibility has found that although students may be aware of many strategies, they often limit their choice to the most efficient one when problem solving [6]. Acknowledging these earlier findings, we identify two ways to improve research on strategic flexibility within ITSs.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations